The economics of environmental risk : information, perception and valuation - Smith, V. K. (Edward Elgar Publishing, 2022)
"Featuring real world examples of how risk information affects public choices, The Economics of Environmental Risk expertly demonstrates that policy makers need to consider how people learn about those risks. Offering insights into examples such as hazardous waste, radon, smoking, hurricanes and terrorist threats over the past four decades, this intuitive book illustrates environmental risks and the choices made to mitigate the potential effects. Providing a deep dive into how public policies and information affect private choices, this book highlights the successes and failings of these choices, recognising how decisions made can have an influence on the hazards that are faced. It also focuses on important lessons to be learnt by officials providing information on risk and designing policies for managing them. Further consideration is also given to how experts understand these risks and how the public interprets the information provided. Scholars and students of public policy, risk analysis and environmental and resource economics will value the useful examples found in this informative volume. Policy makers in risk and insurance, and risk management programs will also find this an instructive guide on the ever-changing environmental risks we face"--